Use of High-Dose Phenylephrine in the Treatment of Ischemic Priapism: Five-Year Experience at a Single Institution. Issue 11 (1st November 2016) - Ridyard, Douglas G.; Phillips, Elizabeth A.; Vincent, William; Munarriz, Ricardo
ABSTRACT: Introduction: Ischemic priapism is an uncommon urologic emergency characterized by a compartment syndrome-like ischemic insult to the corpora cavernosa of the penis. The goal of treatment in ischemic priapism is rapid detumescence to prevent long-term erectile dysfunction. Non-surgical treatment options include aspiration, irrigation, and intracavernous injections of sympathomimetic agents. At our institution, phenylephrine is used in the treatment of ischemic priapism at concentrations and doses that are higher than those recommended in established guidelines. Aim: To characterize our experience with high-concentration intracavernous phenylephrine in the treatment of ischemic priapism at an urban tertiary care center. Methods: A retrospective chart review identified 58 unique patients presenting to the emergency department on 136 occasions and receiving the diagnosis of ischemic priapism by urologic physicians. Patients' charts were reviewed to record the dosing of phenylephrine and the outcomes and circumstances of the presentation. Main Outcome Measures: Success rates of different treatment strategies for different circumstances of presentation. Results: Successful detumescence was achieved with non-surgical management in 86% of unique patients and the overall resolution rate when including repeat visits was 94%. All patients presenting within less than 36 hours of priapism were successfully treated with non-surgical management. There were no reported complications or associated symptoms related to the use of intracavernous phenylephrine during the 5-year period. Conclusion: The use of high concentration and dosing of intracavernous phenylephrine demonstrates a high success rate in the treatment of ischemic priapism. Future prospective studies are needed to further characterize appropriate phenylephrine dosing for its efficacy and safety.